The The Influence of Accounting Information Systems Cash Flow Control in Hospital in The City Medan - Afifah, Alya Nur; Nindiasari, Avininda Dewi (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
The corona virus pandemic has significantly impacted the cash flow of companies in Indonesia. In this study aims to be able to analyze accounting information systems on cash flow control in 15 hospitals in Medan, North Sumatera. Efforts to maintain the strategic and how to control cash flow in the Medan city hospital, the factors that influence the cash flow. The company in order to maintain or increasing more attention to accounting information systems because it has very important role in the company so that the growth or development of the company in line with its vision and mission. This study aims to determine whether there is a significant influence between accounting information systems on cash flow control at hospitals in the city of Medan. This research was conducted using quantitative methods, and data collection was carried out using primery data obtained from the company's accounting information system and cash flow reports. The population of this study was 47 financial employees out of 150 financial employees spread over 15 hospitals in the city of Medan. The results of this study used a purposive sampling test which showed that there was that accounting information systems have significant influence on cash flow control in 15 hospitals in the city of Medan. This paper is a pioneering initiative in assessing the influence of the accounting system information on cash flow report in 15 hospitals in the city of Medan after the Covid-19 pandemic.